Evaluating the impact of species and glue spread rate on hybrid plywood bonding strength - Yo Evy Ivana Samih; Raja Nadhrah Zuhairah Raja Shahrulnizam; Noor Syazwani Idrus; Awang Ahmad Mohd Yunus; Melissa Sharmah Gilbert Jesuet; Muhammad Aizat Abd Ghani; Roziela Hanim Alamjuri; Naruhito Hori; Akio Takemura; Ismawati Palle (the Korean Society of Wood Science and Technology, 2025)
In this study, we investigated how glue spreading rate and veneer species influence the bonding performance of three-layered hybrid plywood comprising Laran (Neolamarckia cadamba) and Red Seraya (Shorea curtisii) veneers at the faces and core, respectively. We bonded hybrid plywood using phenol formaldehyde (PF) resin at spreading rates of 200, 220, and 240 g/m2. For comparison, we also prepared control samples of three-layered plywood made of 100% Laran and 100% Red Seraya, bonded with PF resin at 220 g/m2. We evaluated veneers for their buffering capacity and wettability, also testing their physical (i.e., moisture content, density, water absorption, and thickness swelling) and mechanical (i.e., elasticity and rupture moduli, as well as shear strength) properties according to ISO standards. We detected significant differences in all properties except for moisture content and shear strength upon BDB pre-treatment. Hybrid plywood demonstrated superior bonding strength compared to 100% Laran plywood, with the high-density Red Seraya core contributing to enhanced mechanical properties. However, a glue spread rate beyond 220 g/m2 induced a decline in mechanical strength, indicating diminishing returns with excess adhesive. These results suggest that while glue spread rate influences plywood properties, species-specific veneer characteristics, such as density and wettability, are key bonding performance determinants.